Effects of vitamin D on serum lipid profile in patients with type 2 diabetes: A meta-analysis of randomized controlled trials. Issue 6 (December 2016) - Jafari, Tina; Fallah, Aziz A.; Barani, Afshin
Summary: Background & aims: The effect of vitamin D on lipid profile in type 2 diabetic patients is controversial. This meta-analysis aimed to assess the effect of vitamin D on serum total cholesterol (TC), triglycerides (TG), low-density lipoproteins (LDL), and high-density lipoproteins (HDL) of these patients to elucidate the subject. Methods: Seven databases were searched and randomized controlled trials (RCTs) assessed the effect of vitamin D on lipid profile published until November 2015 were identified. Un-standardized mean difference and its corresponding 95% confidence interval (CI) was calculated from the effect sizes by using random effects model. Results: We found 2220 articles in our systematic search, after exclusion of un-related studies we enrolled 17 studies comparing intervention group (received vitamin D) with control group (received placebo) in the meta-analysis. Vitamin D significantly reduced serum TC (−3.74 mg/dl, 95% CI: −7.13 to −0.34, P  = 0.031), but serum TG did not show significant reduction (−4.90 mg/dl, 95% CI: −15.11–5.31, P  = 0.347). Results confirmed the significant lowering effect of vitamin D on LDL in patients with T2D (−2.55 mg/dl, 95% CI: −4.83 to −0.26, P  = 0.029), but change in serum HDL was negligible (−0.72 mg/dl, 95% CI: −1.27 to −0.17, P  = 0.010). Subgroup analyses showed that the baseline serum 25-hydroxy vitamin D of patients, vitamin D dosage, intervention duration, and the method of vitamin D application influence the effect of vitamin D on lipid markers. Conclusion: This study demonstrated that vitamin D improved serum levels of TC, TG, and LDL in patients with T2D but changes of serum HDL was not satisfactory.